Agricultural ambience and salt stress in production of yellow passion fruit seedlings - Nojosa Lessa, Carla Ingryd; Gomes de Sousa, Geocleber; Castelo Sousa, Henderson; Barbosa da Silva, Fred Denilson; Primola Gomes, Silas; de Araújo Viana, Thales Vinicius (Comunicata Scientiae, 2022)
The objective was to evaluate the initial growth and gas exchange of yellow passion fruit seedlings irrigated with saline water under different environments. The experiment was conducted of the University of International Integration of Afro-Brazilian Lusophony, Redenção-CE. The experimental design used was entirely randomized, in factor arrangement 4 x 2, referring to four environments with different shade screens (black screen; white screen; red screen; all with 50% shading; and full sun) and the values of electrical conductivity of irrigation water (0.3 and 3.0 dS m-1), with five repetitions. The following variables were evaluated: number of leaves, plant height, leaf area, photosynthesis, transpiration, stomach conductance, instantaneous water use efficiency, electrical conductivity of the saturation extract and soil pH. The environment with black screen provides greater performance in leaf area, plant height and root length and was more efficient for the production of dry mass of the aerial part and the root of passion fruit seedlings in both irrigation waters. The red screen environment stimulates greater photosynthesis, transpiration, stomach conductance and chlorophyll in passion fruit seedlings irrigated with low salinity water, while the black screen mitigated saline stress for these variables. The full sun environment provided greater instantaneous water use efficiency in passion fruit seedlings for treatment with low salinity water and the black screen environment with high salinity water.